Superior protection elicited by live-attenuated vaccines in the murine model of paratuberculosis. Issue 51 (16th December 2015) - Ghosh, Pallab; Shippy, Daniel C.; Talaat, Adel M.
Highlights: Novel vaccines are needed to control Johne's disease distressing the dairy industry. LAVs provide protection against M. paratuberculosis by stimulating host immunity. Δ sigH LAV was safe and highly immunogenic in murine model of paratuberculosis. Δ sigH LAV performed better than the available licensed vaccine for Johne's disease. The used approach could be useful against other intracellular pathogens. Abstract: Mycobacterium avium subspecies paratuberculosis ( M. paratuberculosis ) causes Johne's disease, a chronic enteric infection in ruminants with severe economic impact on the dairy industry in the USA and worldwide. Currently, available vaccines have limited protective efficacy against disease progression and does not prevent spread of the infection among animals. Because of their ability to elicit wide-spectrum immune responses, we adopted a live-attenuated vaccine approach based on a sigH knock-out strain of M. paratuberculosis (Δ sigH ). Earlier analysis of the Δ sigH mutant in mice indicated their inadequate ability to colonize host tissues, unlike the isogenic wild-type strain, validating the role of this sigma factor in M. paratuberculosis virulence. In the present study, we evaluated the performance of the Δ sigH mutant compared to inactivated vaccine constructs in a vaccine/challenge model of murine paratuberculosis. The presented analysis indicated that Δ sigH mutant with or without QuilA adjuvant is capable of eliciting strong immune responses (such as interferon gamma-γ, IFN-γ) suggesting their immunogenicity and ability to potentially initiate effective vaccine-induced immunity. Following a challenge with virulent strains of M. paratuberculosis, Δ sigH conferred protective immunity as indicated by the reduced bacterial burden accompanied with reduced lesions in main body organs (liver, spleen and intestine) usually infected with M. paratuberculosis. More importantly, our data indicated better ability of the Δ sigH vaccine to confer protection compared to the inactivated vaccine constructs even with the presence of oil-adjuvant. Overall, our approach provides a rational basis for using live-attenuated mutant strains to develop improved vaccines that elicit robust immunity against this chronic infection.